Comparison of weight, depth, and diagnostic adequacy of specimens obtained with 16 different biopsy forceps designed for upper gastrointestinal endoscopy. Issue 3 (March 1985) - Danesh, B J; Burke, M; Newman, J; Aylott, A; Whitfield, P; Cotton, P B
Abstract : The influence of endoscopic forceps variables (size, design, and make) on biopsy specimen weight, depth, and diagnostic adequacy has been studied in vitro on normal human stomach, and in vivo at endoscopy in dog and in patients. Greater pressure during the biopsy procedure yielded significantly heavier, deeper, and histologically more acceptable specimens. Standard sized forceps (diameter 2.4 mm) and those with ellipsoid cups consistently produced larger specimens than the smaller 'paediatric' forceps (1.8 mm) and those with round cups. Deeper specimens were also obtained using the standard forceps. In vitro and in vivo in the dog, the standard sized forceps also produced specimens of greater diagnostic adequacy than the paediatric forceps. At endoscopy in patients, however, we could not detect any influence of the size, shape, and presence of forceps spike or fenestration on the diagnostic adequacy of the specimens.